PENERAPAN SISTEM AKUNTANSI DAN PERPAJAKAN BERBASIS SAK ETAP DAN PP NOMOR 46 TAHUN 2013 BAGI UMKM - Nofianti, Nana; Mulyasari, Windu (Jurnal Pengabdian Dinamika, 2018)
The purpose of this activity is to provide training on financial reporting and tax calculation for SMEs. Micro, Small and Medium Enterprises (SMEs) in need of bookkeeping and accounting skills are easy to apply in order to prepare financial statements in accordance with Financial Accounting Standards (SAK) ETAP 2011 and can carry out tax obligations to the State in accordance with Regulation 46 of 2013.Problems faced by SMEs is required to prepare financial statements and conduct of tax obligations. While SMEs are not or less capable of making financial statements and therefore can not know the financial position, financial performance, owners' equity in the past and carry out tax obligations. To facilitate SMEs in financial reporting and tax calculation, it takes a simple bookkeeping accounting standards based on the current and the calculation of tax for SMEs.Partners in community service activities are the SMEs in Serang. The method of this activity by providing training in financial reporting and tax calculations.